The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1590/s1519-99402018000200003
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative anatomy and in situ ruminal degradation parameters of elephant grass under different defoliation frequencies

Abstract: SUMMARY This study aimed to determine the area occupied by different tissues present in the leaf blade and the in situ degradability of leaf and stem of elephant grass (Pennisetum purpureum Schum.) under different defoliation frequencies (30, 45, 60, 75 and 90 days). Plants were classified into three levels of insertion in the tiller (apical, medial and basal). The results were presented as a proportion of the area of each tissue in relation to the total area of the leaf blade, namely, parenchyma tissue (PT), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…The correlation between NDF and LIG (Table 4) was significant (r = -0.64) corroborating with Van Soest (1994) and Gallo, Moschini, Cerioli, and Masoero (2013), who demonstrated that there is an increase on the lignin content of fibrous portion. Sanchês et al (2018) analyzed the association of the degradability and their correlations with the anatomical components. The authors verified that the younger the forage, the higher the digestibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The correlation between NDF and LIG (Table 4) was significant (r = -0.64) corroborating with Van Soest (1994) and Gallo, Moschini, Cerioli, and Masoero (2013), who demonstrated that there is an increase on the lignin content of fibrous portion. Sanchês et al (2018) analyzed the association of the degradability and their correlations with the anatomical components. The authors verified that the younger the forage, the higher the digestibility.…”
Section: Discussionmentioning
confidence: 99%
“…High significant correlations among the proportion of individual tissues (epidermis, ground and vascular tissues), or its combination, and the nutritional values suggested that, in general, plant tissues which digestion is rapid, such as the mesophyll tissue, display a positive correlation with the digestibility coefficients and the levels of CP, and a negative correlation with the levels of the cell wall (Sanchês et al, 2018). On the other hand, tissues resistant to digestion such as xylem vessels and sclerenchymatous tissue, or which digestion is partial and slow, as the parenchymatic bunches of the stems display a positive correlation with the lignin contents and a negative correlation with the digestibility (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…After the cutting of standardization, the plots were cut in accordance with the frequencies of preestablished cutoffs (30,45,60,75, and 90 days), on the day of completion of cutting, evaluation was conducted by the monitoring of light interception by the canopy, using the analyzer -AccuPAR Linear PAR/LAI ceptometer, Model . Readings were performed at four sampling points per plot, taking in each location one reading above and one below the canopy, using a reference height of 25 cm (SANCHÊS et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Analyzing the fractions within the frequencies, there was no significant difference (P > 0.05) in the NDF content at a frequency of 30 days; this result is explained by the high incidence of new material and material still in development. Sanchês et al (2018) observed that in plants of elephant grass, as the cells mature, the production of potentially digestible components tends to decrease, and the fiber content increases with advancing of the stage of maturation of the forage harvester, and natural senescence occurs, contributing to increased lignification.…”
Section: Characteristicmentioning
confidence: 99%
See 1 more Smart Citation